Os desafios do ensino de matemática nas turmas do 5º Ano do ensino fundamental no contexto das escolas públicas do Município de Rorainópolis, Roraima - Silva, Luciano Moreira dos Santos (Universidade Federal de Roraima, 2023)
This study was developed in the research line Teacher Training and Educational Practices of the Graduate Program in Education at the Federal University of Roraima - UFRR. It aims to analyze the challenges faced by teachers in teaching Mathematics in 5th grade classes in Public Schools in the city of Rorainópolis - Roraima. This was field research, carried out through a qualitative approach, using as instruments of data collection the questionnaire and the semi-structured interview, both addressed to teachers of 5th grade classes in the city of Rorainópolis. The data collected were analyzed through the Textual Discourse Analysis - TDA, which was developed in three phases, the first being the unitarization process, which consisted of deconstructing the texts into units of meaning. In the second phase of the TDA, the categorization process was developed, and the units of meaning were sorted and grouped into units of similar meanings. The last phase of the TDA consisted in the process of elaborating the meta-texts through the final categories that were transformed into a set of texts with the purpose of seeking to express new understandings about the theme of the study. The research revealed that the main challenges faced by multipurpose teachers in the teaching of mathematics in the city of Rorainópolis can be summarized in three main areas: the lack of mathematical training of multipurpose teachers, the lack of teaching strategies and resources for teaching mathematics, and the absence of family support for school activities. This study contributed to our understanding of the challenges of mathematics teaching that multipurpose teachers experience in their daily lives, from the teachers' perspective.